Increasing the reliability of evaluating information parameters of the adaptive potential due to the use of hottelings cards - Іванець, Ольга Борисівна; Архирей, Марина Володимирівна; Мельников, Олег В’ячеславович; Якимець, Ірина В’ячеславівна (Science-based technologies, 2021)
The paper proposes an approach to assessing the state of the organism by determining the adaptive potential. The functional state of the organism can be assessed by the degree of adaptation to environmental conditions, and since the degree of adaptation is determined by the body's response to environmental influences this assessment also contains a prognostic component. The instantaneous balance between the state of the organism and the environment, which is determined by the stock of functional reserves, is considered as the current functional state of the organism. The functions of the organism are maintained in a state of equilibrium only when the conditions of the external environment fully meet its needs. If the conditions of the external environment, including production, change, become unfavorable, complicate its vital functions, then to counteract them the body directs special mechanisms that maintain the stability of the internal environment or change it within the limits set by physiological laws. Such mechanisms of adaptation (adaptation) are a dynamic process due to which the body maintains the constancy of the internal environment in a changing external environment. Therefore, the assessment of the adaptive reserves of the organism must be considered together with the conditions of external influence as one of the components of the current functional state of the organism. Thus the quantitative estimation of adaptive possibilities needs to be carried out taking into account correlation of separate parameters which are components of the given estimation.The paper proposes to improve the method of estimating the adaptive reserves of the organism by determining the adaptive potential using Hotelling maps, which allow to test the hypothesis of biological stability of the objects of study. It was found that the use of Hotelling maps for the evaluation of such complex systems as the human body gives more reliable results compared to existing methods. The use of the approach taking into account the adaptive potential with the use of Hottelling maps, to determine the disorder of biological objects, allows us to conclude that the adaptation reserves and the functional state of the organism. This is especially important for deciding on the professional suitability of professions with extreme external destabilizing factors